Niuailan, a new genus to accommodate Carneoryctes peterseni (Endrődi, 1967) (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini) from New Ireland, Papua New Guinea - Allsopp, Peter G.; Hutchinson, Paul M. (Zootaxa, 2020)
Niuailan new genus is established for Cryptoryctes peterseni Endrődi, 1967 (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini) from New Ireland, Papua New Guinea. Characters distinguishing it from the Australian Carneoryctes Özdikmen, 2009 species are discussed. The combination of dilated metatibiae, shape of the clypeus and pygidium, simply curved mandibles, absence of a frontal horn, tubercle or carina, and three pronotal horns in Niuailan allow clear separation from other New Guinea Pentodontini.